Peningkatan Hasil Belajar Siswa melalui Pembelajaran Discovery Learning Muatan IPA Semester 1 pada Kelas VI SDN 195/VI Pematang Kancil - Kurniawan, Dandi; Maulana, Irsyad; Ouralita, Silvi; Rindiani, Gusnia; Hestiana, Syafrida Dwi; Nabila, Nabila (Lembaga Yasin AlSys, 2022)
The implementation of teaching and learning activities can be carried out using various methods, models, approaches, and media according to the needs of teachers and students. Various methods, models, approaches, and media will make learning more meaningful, and the delivery of material will be easier. Based on the facts in the field there are still many educators who carry out a monotonous learning process, especially in science material, so that it seems boring to students such as at SDN 195/VI Pematang Kancil, so that student learning outcomes decrease. The main purpose of making this journal is to analyze related to improving student learning outcomes through discovery learning science content semester 1 in class VI SDN 195/VI Pematang Kancil. Writing this journal is based on a type of qualitative research using a literature review approach or literature review. Library review is an activity to examine various forms of relevant sources. The conclusion is that using the Discovery Learning learning model in Natural Education subjects at the elementary level is effective in improving student learning outcomes. The aspects in the indicators of student learning outcomes include cognitive, psychomotor, and also affective aspects.